An evaluation of changes in the crawl-stroke technique during training periods in a swimming season - Arellano, R.; Pardillo, S. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
In an effort to determine changes in swimming stroke mechanics over the seasonal training period, a study was initiated to evaluate the degree of change following every mesocycle in the training season (four-month macrocycle training period). Twenty-two average and high level swimmers were evaluated after three different training periods. The swimming movements in the crawl-stroke were recorded underwater and digitized to determine kinematic parameters. The forces generated during a tethered swimming test were sensed using a force transducer. Other kinematic parameters measuring stroke length, stroke frequency and average speed over 50 m of crawl-stroke were analyzed. Analysis of variance with repeated measures showed significant differences in 50 m time (T50), average speed (AV) and maximal force during ten strokes and 30 s efforts. Our findings support the suggestion that improvements in short distance results are closely related to improvements in strength measured during tethered swimming. This type of evaluation would help in effecting better control of the adaptations brought about by specific strength training.